Complement Inhibition in a Xenogeneic Model of Interactions Between Human Whole Blood and Porcine Endothelium - Kourtzelis, I.; Ferreira, A.; Mitroulis, I.; Ricklin, D.; Bornstein, S. R.; Waskow, C.; Lambris, J. D.; Chavakis, T. (Hormone and Metabolic Research, 2015)
Xenotransplantation (xeno-Tx) is considered as an alternative solution to overcome the shortage of human donor organs. However, the success of xeno-Tx is hindered by immune reactions against xenogeneic cells (e. g. of porcine origin). More specifically, activation of innate immune mechanisms such as complement and triggering of the coagulation cascade occur shortly after xeno-Tx, and adhesion of human leukocytes to porcine endothelium is another early critical step mediating the immune attack. To investigate the therapeutic potential of complement inhibition in the context of xenogeneic interactions, we have employed a whole-blood model in the present study. Incubation of human blood with porcine endothelial cells (PAECs) led to activation of complement and coagulation as well as to increased leukocyte adhesion. The observed responses can be attributed to the pig-to-human xenogeneicity, since the presence of human endothelium induced a minor cellular and plasmatic inflammatory response. Importantly, complement inhibition using a potent complement C3 inhibitor, compstatin analogue Cp40, abrogated the adhesion of leukocytes and, more specifically, the attachment of neutrophils to porcine endothelium. Moreover, Cp40 inhibited the activation of PAECs and leukocytes, since the levels of the adhesion molecules E-selectin, ICAM-1, ICAM-2, and VCAM-1 on PAECs and the surface expression of integrin CD11b on neutrophils were significantly decreased. Along the same line, inhibition of CD11b resulted in decreased leukocyte adhesion. Taken together, our findings provide a better understanding of the mechanisms regulating the acute innate immune complications in the context of xeno-Tx and could pave the way for complement-targeting therapeutic interventions.
Keywords: complement C3; xenotransplantation; leukocyte adhesion; compstatin